2016
DOI: 10.1371/journal.pone.0164840
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prognosis of Anaplastic Thyroid Carcinoma: A Clinical Study of 50 Cases

Abstract: IntroductionAlthough anaplastic thyroid carcinoma (ATC) is rare, it is one of the most aggressive human cancers. The optimal multimodal therapy policy of ATC is still debated, and a standardized treatment strategy remains to be established. This study aimed to evaluate the management aspect and prognosis of ATC.Materials and MethodsThe data were analyzed retrospectively for 50 patients with ATC to evaluate the clinical characters, management and factors influencing survival. Survival analysis was performed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
0
31
1
Order By: Relevance
“…One of the features of ATC is the aggressive invasion of the thyroid capsule, adjacent structures, early lymph nodes and distant spread. In this study, there was a small number of patients with invaded recurrent laryngeal nerve (5/30 patients), trachea (5/30 patients), and strap muscles (4/30 patients), contrary to Liu et al where 31/50 patients had invasion of the surrounding structures 16 . The incidence of metastases at presentation was 40% which is less than that in the study by Aslan et al (55%, 16/29) where 8 patients presented with metastases and 8 patients developed it shortly after 27 .…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…One of the features of ATC is the aggressive invasion of the thyroid capsule, adjacent structures, early lymph nodes and distant spread. In this study, there was a small number of patients with invaded recurrent laryngeal nerve (5/30 patients), trachea (5/30 patients), and strap muscles (4/30 patients), contrary to Liu et al where 31/50 patients had invasion of the surrounding structures 16 . The incidence of metastases at presentation was 40% which is less than that in the study by Aslan et al (55%, 16/29) where 8 patients presented with metastases and 8 patients developed it shortly after 27 .…”
Section: Discussioncontrasting
confidence: 69%
“…Univariate and multivariate analyses of factors affecting survival by Kihara et al showed that complete surgery was an independent prognostic factor 43 . Other reports also found that complete resection was associated with longer survival compared to incomplete surgery or biopsy 14,16 . Sun et al reported on treatment and prognosis of 60 patients diagnosed with ATC 14 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations